Preparation of Antimicrobial Halal Gelatin/Curcumin Composite Films For Active Food Packaging Applications - Mohd, Farah Syahirah; Basri, Hatijah (Enhanced Knowledge in Sciences and Technology, 2022)
The Halal status of development of plastic packaging made from animal gelatin is often questionable. Therefore, the alternative source of halal gelatin is required in order to replace the use of pork gelatin with gelatin obtained from marine sources. Gelatin from the warm-blooded fish has similar properties to mammalian sources. The scales of fish are known to be high in collagen that can be a good source of gelatin. In this study, gelatin was extracted from the tilapia scales by heating the scales in distilled water at 70℃. Besides, the incorporation of curcumin in the gelatin-based films for the applications of active food packaging is known to have potential to exhibit the antimicrobial properties. The halal gelatin/curcumin composite films were prepared by using glycerol as plasticizer and sodium dodecyl sulphate (SDS) as an emulsifier. The neat gelatin and gelatin/curcumin composite films were characterised by using field emission scanning emission microscopy (FE-SEM) and Fourier transform infrared spectroscopy (FTIR). The FE-SEM results showed that the low concentration of curcumin was dispersed evenly in the matrix of gelatin but not well dispersed at high concentration of curcumin. The FTIR analysis of neat gelatin and gelatin/curcumin composite films showed no significant changes in the functional group of the composite films even after the addition of SDS and curcumin. All the film samples has a significant difference on the L* a* and b* values (p ˂ 0.05). In this study, the incorporation of curcumin into gelatin films did not exhibit the antimicrobial activity against the foodborne pathogenic bacteria, Escherichia coli (E. coli) and Staphylococcus aureus (S. aureus).